Rancang Bangun Sistem Informasi Pelayaran Kapal Antar Pulau - Pramana, Rozeff; Harahap, Ilman Fauzi (Fakultas Teknik Universitas Maritim Raja Ali Haji, 2017)
One of the factors that caused the ship accident was extreme weather conditions. The absence of a device that can provide real time weather information for port systems and the departure of inter-island vessel ships that make the voyage less secure. The purpose of this study is to provide information related to weather conditions such as current direction, current velocity, wind direction, wind speed and wave height to the ships captain and passenger ship. The toolkit consists of current velocity meter, wind speed gauge, current direction detection, wind direction detection and wave height meter. This inter-island information system device uses hall effect sensor and ultrasonic sensor. The sensor readings will be processed using Arduino Uno which is integrated with GSM Shield and then sent to the internet. Data residing on the internet will be monitored using Raspberry PI.